2022
DOI: 10.3389/fmars.2022.1001180
|View full text |Cite
|
Sign up to set email alerts
|

The importance of relational values in gaining people’s support and promoting their involvement in social-ecological system management: A comparative analysis

Abstract: People’s support and involvement are critical to the sustainable use and conservation of social-ecological systems (SESs). Integrating people’s values into management decisions is pivotal. Without proper integration, the resulting SES may not align with their desires and may not be supported by people. Furthermore, values can be a deep leverage point within a system that is difficult to change, as people may be more willing to be involved in activities that support what they value. Recent studies have illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…This ensures the welfare of both the mountain and people. As found in previous studies in this area (Uehara et al, 2022;Yuliani et al, 2022), the herein relational values are closely interrelated to both instrumental and intrinsic values highlighting the relevance of value plurality in biocultural conservation contexts. For example, religious tourism as a major part of the top important instrumental values tightly intersects with the intrinsic spirituality or sacredness of the mountain that is often acknowledged as an important component of the moral psychology of the human-nature relationship (Marsuki, 2009;Spoon, 2011;Billet et al, 2023).…”
Section: Vrk Perception and Interplaysupporting
confidence: 71%
See 1 more Smart Citation
“…This ensures the welfare of both the mountain and people. As found in previous studies in this area (Uehara et al, 2022;Yuliani et al, 2022), the herein relational values are closely interrelated to both instrumental and intrinsic values highlighting the relevance of value plurality in biocultural conservation contexts. For example, religious tourism as a major part of the top important instrumental values tightly intersects with the intrinsic spirituality or sacredness of the mountain that is often acknowledged as an important component of the moral psychology of the human-nature relationship (Marsuki, 2009;Spoon, 2011;Billet et al, 2023).…”
Section: Vrk Perception and Interplaysupporting
confidence: 71%
“…Hermon and people (Arias-Arévalo et al, 2017; Himes & Muraca, 2018). This con rms the vital role of biocultural relational values in conservation decision making and high potential for care and stewardship actions of community towards the mountain (Mattijssen et al, 2020;Arias-Arévalo et al, 2018;Topp et al, 2021;Uehara et al, 2022). This ensures the welfare of both the mountain and people.…”
Section: Vrk Perception and Interplaymentioning
confidence: 80%
“…By generating affective and cognitive experiences of nature (Section IV), wild spaces also have the potential to develop relational values of nature such as spiritual and aesthetics experiences and ecological knowledge (Chan et al ., 2016; Himes & Muraca, 2018). It has been suggested that relational values can serve as leverage points for changes towards nature connection and conservation actions (Bekessy et al ., 2018; Mattijsen et al ., 2020; Russo Lopes & Bastos Lima, 2023; Uehara, Sakurai & Hidaka, 2022). We can therefore expect the development of wild urban spaces in urban planning to be a pathway for improving human–nature connections.…”
Section: Urban Wilding In the Fabric Of Just Citiesmentioning
confidence: 99%
“…Every SES requires a suitable system boundary to effectively identify management implications and facilitate comparisons [47]. This is crucial because a SES should encompass the relevant ecological systems essential for maintaining key biophysical structures and processes.…”
Section: Aspect 1: Geographical Characteristicsmentioning
confidence: 99%